DETERMINAN KINERJA SISTEM INFORMASI AKUNTANSI DI LPD KECAMATAN GIANYAR - Ernawatiningsih, Ni Putu Lisa; I Ketut Sunarwijaya (Jurnal Riset Akuntansi, 2024)
The performance of a financial institution is largely determined by the performance of its accounting information system, because it will produce quality financial reports. The purpose of this research is to test and analyze the influence of variables using information technology, leadership, education and training, organizational culture, and work experience on the performance of accounting information systems at Village Credit Institutions in Gianyar District. The research sample consisted of 78 employees who were identified using the purposive sampling method. The data analysis method used in this research is multiple regression analysis. This research found that education and training, organizational culture, and work experience had a positive effect on the performance of the accounting information system, while the use of information technology and leadership had no effect on the performance of the accounting information system.